Respuesta :
Answer:
6x² - 7x - 3
Step-by-step explanation:
(f × g)(x) = f(x) × g(x), that is
(2x - 3)(3x + 1)
Each term in the second factor is multiplied by each term in the first factor, that is
2x(3x + 1) - 3(3x + 1) ← distribute both parenthesis
= 6x² + 2x - 9x - 3 ← collect like terms
= 6x² - 7x - 3
The value of [tex]f(g(x))=-6x-5[/tex]
Composite function :
Given functions are, [tex]f(x)=-2x-3,g(x)=3x+1[/tex]
We have to find composite function [tex]f(g(x))[/tex].
[tex]f(g(x))=f(3x+1)\\\\f(g(x))=-2(3x+1)-3\\\\f(g(x))=-6x-2-3\\\\f(g(x))=-6x-5[/tex]
Learn more about the composite function here:
https://brainly.com/question/10687170